PELAPORAN SURVEILANS DEMAM BERDARAH BERBASIS SMS DI KOTA YOGYAKARTA - Anwar Dwi Cahyono; Tri Baskoro Tunggul Satoto; Lutfan Lazuardi (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: The need of accurate and accelerate information lead to decision making in order to dengue treatment now a days is high in Yogyakarta City Government. This was related to the fact that there is a delay more than 24 hours from patient is diagnosed with dengue until the case was reported from hospital. Objective: to describe dengue surveillance report using SMS gateway. Methods: This research is using qualitative approach. Respondent from this research are Head of Disease Control Department, Head of Health Promotion and Health Information System and the others are hospital staffs who is responsible for dengue reporting. Result: SMS based reporting does not show the real amount number of dengue cases for a year, during the implementation there has been 187 cases from the SMS. This was far beyond the real number of cases which is 411 cases. Conclusion: This SMS based for dengue surveillance reporting cannot be the information that can lead to decision making.